Atlas of robotic cardiac surgery - Chitwood, W. Randolph, Jr; Dodson, Rebekah (Springer, 2014)
This comprehensive atlas defines the role of robotic surgery in cardiac surgical practice and provides a wealth of practical didactic advice. The Editor has assembled a group of experts in the field to define the complete operative pathway of each procedure for surgeons who desire to become a complete robotic cardiac surgeon. To reduce the learning curve, the atlas includes hints and procedure pitfalls that are derived from the experiences of the chapter contributors. The most important cardiac operations, including valve repair and replacement as well as coronary surgery, are detailed but using the latest robotic methods. Atlas of Robotic Cardiac Surgery is richly illustrated with the highest quality illustrations. Anaesthesia and cardiopulmonary support preparation for each operation is featured, and selected references have been provided to emphasize evidence-based outcomes from previously published data. As such, this book will influence and be essential reading for both practicing and trainee surgeons in minimally invasive and robotic cardiac surgery.